2019
DOI: 10.17222/mit.2018.051
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of low-alloy steel used for flexible pipes exposed to a seawater environment

Abstract: An immersion experiment was carried out to illustrate the corrosion behavior of low-alloy steel used for flexible pipes in a seawater environment in terms of corrosion kinetics, corrosion phases, surface morphology, cross-sectional morphology and elemental distribution. The experimental results show that the corrosion rate with an exponential format is linear with respect to the corrosion time with an exponential format. The main corrosion phases are goethite (a-FeOOH), lepidocrocite (g-FeOOH), iron oxide (Fe2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The Cu 2+ /Cu + ions released during the electrochemical corrosion process of T2 in sea water would destroy biological cells. When Cu 2+ /Cu + ions reached a certain concentration, it could effectively kill sea creatures and prevent their growth on the surface [18,19]. In particular, Cu 2 O formed on the surface played a crucial role in inhibiting marine biofouling [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cu 2+ /Cu + ions released during the electrochemical corrosion process of T2 in sea water would destroy biological cells. When Cu 2+ /Cu + ions reached a certain concentration, it could effectively kill sea creatures and prevent their growth on the surface [18,19]. In particular, Cu 2 O formed on the surface played a crucial role in inhibiting marine biofouling [20].…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from Table 3, the corrosion rate of 12832 copper alloy was less affected by these sea water environmental factors such as pH, salinity and temperature, but the surface fouling conditions (including sediment deposition) had a crucial impact. On the one hand, XRD results showed that the content of Cu 2 O in the corrosion products of 12832 copper alloy was very small, and the dealloying corrosion products played a role of physical isolation, which contributed to the occurrence of biofouling [18,19,22]. On the other hand, only when the corrosion rate of copper alloys reaches 0.025 mm y −1 , a better antifouling effect can be achieved [1,23].…”
Section: Discussionmentioning
confidence: 99%